Case study on C.K. Tang Ltd. - Chia, Sok Luan. (2008)
This case looks at C.K. Tang's marketing strategy as it struggles to thrive amidst the current economic meltdown. It is based in a model of the retail exchange environment. Using a SWOT and a survey as a framework of analysis, the case assesses C.K. Tang's performances during this period.